Phase analysis in maximal sprinting: an investigation of step-to-step technical changes between the initial acceleration, transition and maximal velocity phases - von Lieres und Wilkau, H. C.; Irwin, G.; Bezodis, N. E.; Simpson, S.; Bezodis, I. N. (Sports Biomechanics, 2020)
The aim of this study was to investigate spatiotemporal and kinematic changes between the initial acceleration, transition and maximum velocity phases of a sprint. Sagittal plane kinematics from five experienced sprinters performing 50-m maximal sprints were collected using six HD-video cameras. Following manual digitising, spatiotemporal and kinematic variables at touchdown and toe-off were calculated. The start and end of the transition phase were identified using the step-to-step changes in centre of mass height and segment angles. Mean step-to-step changes of spatiotemporal and kinematic variables during each phase were calculated. Firstly, the study showed that if sufficient trials are available, step-to-step changes in shank and trunk angles might provide an appropriate measure to detect sprint phases in applied settings. However, given that changes in centre of mass height represent a more holistic measure, this was used to sub-divide the sprints into separate phases. Secondly, during the initial acceleration phase large step-to-step changes in touchdown kinematics were observed compared to the transition phase. At toe-off, step-to-step kinematic changes were consistent across the initial acceleration and transition phases before plateauing during the maximal velocity phase. These results provide coaches and practitioners with valuable insights into key differences between phases in maximal sprinting.